The Effects of Early Education Backgraund and Socioeconomic Factors of Students' Academic Performance in Azerbaijan - Sideifzada, Fidan (My University, 2016)
The study examined the effects of early education background and two socioeconomic factors, which are parental education and family budget, on the academic performance of students in Azerbaijan. The multiple sampling techniques were used to select 618 students from 19 Universities and to administer the questionnaire. The data on student's academic performance was obtained from student's scores in entrance examination and also from an Indicator of Total Average Achievement of students for first year undergraduate education. Data obtained was analyzed using both descriptive and inferential statistical techniques: two-sample t test, one-way ANOVA and multiple linear regression. The results of hypothesis testing revealed a positive and statistically significant relationship between mother's education and both dependent variables. Moreover, the budget of family is in positive relationship with the ITAA results of the students and the result is statistically significant. However, the outcomes of the study show that kindergarten preschool education negatively affect the academic performance of the students and for dependent variable score in entrance exam the result is statistically significant.
Keywords: Public and International Affairs; Education -- Azerbaijan; Academic Performance -- Azerbaijan; Kindergarten Preschool Education -- Azerbaijan; Socioeconomic Factors -- Azerbaijan; Parental Education -- Azerbaijan; Budget of Family -- Azerbaijan